2019
DOI: 10.2174/1573412914666180716143939
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Capillary Electrophoresis Characteristic Fingerprint of Schisandra chinensis

Abstract: Background: The quality control indexes detected by the existing methods are less and lack specificity, and cannot truly reflect their intrinsic quality because of the similarity of Schisandra chinensis and Schisandra sphenanthera in both their appearance and their main chemical composition. Therefore, it is urgent to establish an effective method for the quality control of the both. High-performance capillary electrophoresis (HPCE) method was used to establish the fingerprints of Schisandra medicinal material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…At present, the common fingerprints of traditional herbal medicine are thin layer chromatography fingerprint (Szeremeta et al, 2017 ; Sibug-Torres et al, 2019a , b ), high-performance liquid chromatography fingerprint (Li et al, 2016 ; Xue et al, 2017 ; Esteki et al, 2019 ), gas chromatography fingerprint (Aliakbarzadeh et al, 2016 ; Shekari et al, 2018 ; Huang et al, 2019 ), high-performance capillary electrophoresis fingerprint (Hou et al, 2019 ; Sun et al, 2019 ), high-speed countercurrent chromatography fingerprint (Gan et al, 2016 ; Wang et al, 2020 ), ultraviolet fingerprint, infrared fingerprint (Custers et al, 2017 ; Dai et al, 2019 ), nuclear magnetic resonance fingerprint (Sun et al, 2018 ; Flores et al, 2020 ), mass spectrometry fingerprint (Yang and Deng, 2016 ; Kharbach et al, 2020 ), X-ray diffraction fingerprint (Chen et al, 2017 ; Devi et al, 2017 ), immunoassay fingerprint (Cui et al, 2019 ), and DNA fingerprint (Pawar et al, 2017 ; Selvakumari et al, 2017 ). These methods can be used for in-depth research on traditional herbal medicine, but proper pretreatment of traditional herbal medicine is required.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the common fingerprints of traditional herbal medicine are thin layer chromatography fingerprint (Szeremeta et al, 2017 ; Sibug-Torres et al, 2019a , b ), high-performance liquid chromatography fingerprint (Li et al, 2016 ; Xue et al, 2017 ; Esteki et al, 2019 ), gas chromatography fingerprint (Aliakbarzadeh et al, 2016 ; Shekari et al, 2018 ; Huang et al, 2019 ), high-performance capillary electrophoresis fingerprint (Hou et al, 2019 ; Sun et al, 2019 ), high-speed countercurrent chromatography fingerprint (Gan et al, 2016 ; Wang et al, 2020 ), ultraviolet fingerprint, infrared fingerprint (Custers et al, 2017 ; Dai et al, 2019 ), nuclear magnetic resonance fingerprint (Sun et al, 2018 ; Flores et al, 2020 ), mass spectrometry fingerprint (Yang and Deng, 2016 ; Kharbach et al, 2020 ), X-ray diffraction fingerprint (Chen et al, 2017 ; Devi et al, 2017 ), immunoassay fingerprint (Cui et al, 2019 ), and DNA fingerprint (Pawar et al, 2017 ; Selvakumari et al, 2017 ). These methods can be used for in-depth research on traditional herbal medicine, but proper pretreatment of traditional herbal medicine is required.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Some studies have shown that S. chinensis can improve the learning and memory disorders of mice, but these studies lacked a systematic approach, and its mechanism was not studied in sufficient depth. 17 In this study, the models of memory acquisition disorder, memory consolidation disorder, memory reproduction disorder, and aging in mice were established by intraperitoneal injection of scopolamine, chloramphenicol, 40% ethanol, and subcutaneous injection of d-galactose, respectively; the improvement of Schisandra chinensis extract (SCE) on the learning and memory disorders induced by the different agents was observed systematically, and the mechanism explored, which was expected to provide a basis for S. chinensis being used as either a medicine or health food.…”
mentioning
confidence: 99%